2019
DOI: 10.1017/aae.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Price Determinants of Performance-Tested Bulls over Time

Abstract: We estimate the values of bull phenotypic traits, performance measurements, and expected progeny differences (EPDs) over time using bull sale data from an auction in Tennessee from 2006 to 2016. Moreover, we determine how a state partial-cost reimbursement program for bulls with certain EPDs affects bull sale price. Purebred seed stock producers in this region should focus on selling large, fast-growing, mature bulls that produce lighter calves for reduced calving stress. The state cost-share payment did not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…A hedonic pricing model was used to determine whether, or not, phenotypic traits and EPD's influence the sale price of bulls (Boyer et al, 2019;Brimlow and Doyle, 2014;Dhuyvetter et al, 1996;Jones et al, 2008;Kessler, Pendell, and Enns, 2017;Vestal et al, 2013). We specify a log-level model by using the log-transformed the sale price to correct non-normal distribution (Wooldridge, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A hedonic pricing model was used to determine whether, or not, phenotypic traits and EPD's influence the sale price of bulls (Boyer et al, 2019;Brimlow and Doyle, 2014;Dhuyvetter et al, 1996;Jones et al, 2008;Kessler, Pendell, and Enns, 2017;Vestal et al, 2013). We specify a log-level model by using the log-transformed the sale price to correct non-normal distribution (Wooldridge, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in milk EPD has also been reported to increase bull sale price (Boyer et al, 2019;Jones et al, 2008;Vestal et al, 2013); however, Kessler, Pendell, and Enns (2017) found the converse to be true. Milk production also requires a higher nutritional demand, which can increase feed costs for a sire's daughters.…”
Section: Hypotheses For Variable Signmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between birth weight and growth rate is positive. As a result, most sires with lower-than-average birth weight EPDs would also have lower-than-average weaning and yearling weight EPDs (Griffith et al, 2020;Boyer et al, 2019; ). There are, however, sires available that are below average in terms of birth weight but above breed average in terms of growth traits.…”
Section: Expected Progeny Difference (Epd) Indicators By Categorymentioning
confidence: 99%